A reflection upon the «new» rights. prospects and challenges in the 21st Century - Fauth, Gabriela (2013)
This paper analyses the paradigm shift that comes from thetransition from Modernity to postmodernity process and the challenges faced today in the legal field. Furthermore, the aim is to reflect upon the so-called«new» rights, focusing on the environmental law and urban planning law, considered the precursors of this postmodern perspective on the law. Finally, it presents its challenges and prospects for the 21st Century.